Keuangan Publik Dan Sumber Daya Manusia - Sadu Wasistiono (Jurnal Administrasi Publik, 2002)
Although decentralization and autonomy is exercised since Indonesian republic is formed, but they are not developed such as in West Countries, because it is not a panacea for the ill state or especially local government. Theoritically, there are many prerequisites of decentralization and autonomy that should called attention to the civil servants whose governed the local government. Many theoriticians written down about decentralization, included the advantages and disadvantages of it, the prerequisites should be fulfilled to apply it.Decentralization means that there are transfer of authority and responsibility in public function from central government to local government, other semi public agenda and also to the private sector. Also there are opinion about form and type of decentralization. The interesting things is the type of decentralization which divided decentralization into 4 types namely political, administrative, fiscal, economic and market decentralization.The aim of fiscal decentralization is to transfer the source of the financial to local such as the right to own and manage their own properties and the right to manage their human resources. But it is restricted by the upper rules, the well being of the people and should be applied properly.Local government give more attention to how they can earn more revenue than how to used it. Actually many infraction is occurred in the expenditures area. Local government is facing constraint with the fiscal decentralization relating with the source of the revenue. Central government still have right to attract revenue from local government, the effect is the state give balance aid to complete APBD (Anggaran Pendapatan dan Belanja Daerah). So central government still become the importance role in public decentralizationThe expenditure part in APBD is consist of two parts, routine budget and development budget. In reality, both of them is used for the sake of the local government itself. Nowadays the routine budget is bigger than development budget. All of this constraint can be suremount if, the local government has human resources that competent in their tasks. Once again central government didn't give a guide to the local government about the national Employee System, the effect is the local government can use by their own way about how to manage their civil servants.